"Fei ke xue" de Zhongguo chuan tong yu tu Zhongguo chuan tong yu tu hui zhi yan jiu = The study on the cartographic method of the Chinese ancient maps - Cheng, Yinong 1974- (Zhongguo she hui ke xue chu ban she, 2016)
Summary in Chinese field only